Localization in Wireless Sensor Networks Based onFuzzy Logic - Monfared, Mostafa Arbabi (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: One of the fundamental problems in Wireless Sensor Networks (WSNs) is the localization of sensor nodes based on the known location of several nodes. In this thesis one of the intelligent localization schemes, which is a range free localization is used to estimate the location of the unknown nodes. In the proposed method, the anchor nodes (reference nodes) are connected to the sensor nodes and then each sensor node receives the signal strength indicator (RSSI) from each of the anchor nodes. The RSSIs are achieved based on the distance of the sensor node to each of anchor nodes. The RSSIs are fed to the sugeno fuzzy inference system to calculate the weights used in the centroid relation. The centroid technique is the range free based localization scheme, which is proposed to estimate the location of the sensor nodes. Both analytical and experimental approaches are considered where the analytical approach is done by sugeno fuzzy inference in the two different environments with and without Additive White Gaussian Noise (AWGN). The experimental method is done for 6 sensor nodes and repeated 6 times in different positions in a region. There is an error of locating the actual and the estimated nodes in both analytical and experimental approaches. The error of location of the estimated sensor nodes in the experimental method is not much in comparison with the analytical method. Keywords: Range free localization, received signal strength indicator, centroid localization, fuzzy logic system and wireless sensor network. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Kablosuz Sensör Ağları (KSA) (“Wireless Sensor Networks” – WSNs - ) konusunda yaşanmakta olan temel sorunlardan biri, bilinen birkaç sensör düğümünün konumlarına istinaden sensör düğümlerinin lokalizasyonudur. Bu tez çalışmasında, bilinmeyen sensör düğümlerinin konumlarının tahmin edilmesi amacıyla, uzaklığa bağlı olmayan bir lokalizasyon yöntemi olan akıllı lokalizasyon planlarından biri kullanılmaktadır. Önerilmekte olan yöntemde, referans sensör düğümleri diğer sensör düğümlerine bağlanmakta ve bundan sonraki aşamada her bir sensör düğümü Sinyal Güç Göstergesini (SGG) (“Signal Strength Indicator” – RSSI - ) her bir referans düğümünden almaktadır. Elde edilen Sinyal Güç Göstergeleri, sensor düğümünün her bir referans sensör düğümünden uzaklığına bağlı olmaktadır. Elde edilen Sinyal Güç Göstergeleri, ağırlık merkezi hesaplama bağıntısında kullanılmak amacıyla ağırlıkları hesaplanmak üzere Sugeno bulanık hesaplama ve sonuçlandırma sistemine verilmektedir. Ağırlık merkezi hesaplama tekniği, sensor düğümlerinin konumlarının tahmin edilmesi için önerilen ve uzaklığa bağlı olmayan baz lokalizasyon tekniklerinden biri olmaktadır. Bu çalışmada hem analitik hem de deneysel yöntemler dikkate alınmış olup analitik incelemeler, Beyaz Gauss Gürültülü (BGG) (“Additive White Gaussian Noise” – AWGN - ) ve Beyaz Gauss Gürültüsüz olmak üzere iki değişik ortamda Sugeno Hesaplama ve Sonuçlandırma Sistemi tarafından gerçekleştirilmiştir. Deneyler 6 sensör düğümü için yapılacak olup bir alandaki 6 farklı konumda tekrarlanacaktır. Hem analitik hem deneysel incelemeler sırasında düğümlerin gerçek konumları ile tahmin edilen konumları arasında bir hata bulunmaktadır. Deneysel çalışmalarda tahmin edilen her bir sensör düğümünün konumu ile gerçek düğüm konumu arasındaki fark analitik incelemeler ile karşılaştırıldığında çok büyük farklılıklar görülmamaktedır. Anahtar Kelimeler: Uzaklığa bağlı olmayan lokalizasyon, Gelen sinyal güç göstergesi, ağırlık merkezi lokalizasyonu, bulanık mantık sistemi ve kablosuz sensor ağı.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2012. Supervisor: Prof. Dr. Şener Uysal.
Keywords: Electrical and Electronic Engineering; Sensor networks; Digital Communication; Fuzzy logic - Engineering Mathematics; Range Free Localization - Received Signal Strenth Indicator; Centroid Localization - Fuzzy Logic System and Wireless Sensor Network